2019
DOI: 10.1038/s41598-018-38214-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity and anticancer effects of citral nanostructured lipid carrier on MDA MBA-231 human breast cancer cells

Abstract: Very recently, we postulated that the incorporation of citral into nanostructured lipid carrier (NLC-Citral) improves solubility and delivery of the citral without toxic effects in vivo. Thus, the objective of this study is to evaluate anti-cancer effects of NLC-Citral in MDA MB-231 cells in vitro through the Annexin V, cell cycle, JC-1 and fluorometric assays. Additionally, this study is aimed to effects of NLC-Citral in reducing the tumor weight and size in 4T1 induced murine breast cancer model. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 77 publications
1
45
0
Order By: Relevance
“…In our previous study, the potential anti-tumor effect of NLC-Citral was ascertained using MDA-MB-231 cells in vitro [12]. In this study, the oral efficacy of NLC-Citral as compared to the citral in suppressing the breast tumor growth was tested in 4T1-challenged mice treated for 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, the potential anti-tumor effect of NLC-Citral was ascertained using MDA-MB-231 cells in vitro [12]. In this study, the oral efficacy of NLC-Citral as compared to the citral in suppressing the breast tumor growth was tested in 4T1-challenged mice treated for 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that citral is a is a key component of the essential oils extracted from lemon balm with antiproliferative effect in several leukemia cell lines (P388, NB4, MOLT-4) via the induction of apoptosis (Xia et al, 2013). Recent study demonstrated that citral nanostructured lipid carrier inhibited the proliferation of breast cancer cells in vitro (MDA MBA-231 human breast cancer cells), majorly through the induction of apoptosis, anti-metastasis, anti-angiogenesis potentials, and reducing the tumor weight and size without altering the therapeutic effects of citral (Nordin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond, citral attracted scientists' attention towards its anticancer properties in a variety of cancer types, such as melanoma [259], colon cancer [260], and breast cancer [261]. Bayala and co-authors provided evidence about Cymbopogon citratus and Cymbopogon gigantescus essential oil cytotoxic activity, which have citral as its major component and significantly decreased prostate and glioblastoma cancer cell survival [262].…”
Section: Citralmentioning
confidence: 99%
“…Initially, they showed that NLC as a drug delivery system for citral has the potential to sustain drug release without inducing any toxicity [269]. Then, they showed that NLC-citral regulated apoptosis, cell cycle, and metastasis signaling, all key signaling pathways related to cancer development [261]. In addition, citral was pointed as a potential effective additive to chemotherapeutic treatment [270,271].…”
Section: Citralmentioning
confidence: 99%